In-situ sonosynthesis of cobblestone-like ZnO nanoparticles on cotton/polyester fabric improving photo, bio and sonocatalytic activities along with low toxicity and enhanced mechanical properties. (1st August 2017) - Rastgoo, Madine; Montazer, Majid; Harifi, Tina; Mahmoudi Rad, Mahnaz
Abstract: For the first time in this study, in-situ sonosynthesis and deposition of ZnO nanoparticles under ultrasound irradiation was used to prepare multifunctional cotton/polyester fabric. The process was carried out at 80 ° C in ultrasonic bath and was free from final heating of fabrics to convert zinc hydroxide to zinc oxide nanoparticles. This was due to the physical and chemical effects of ultrasound promoting the involved reactions and facilitating the nucleation and growth of ZnO nanoparticles. Central composite design was also used to statistically analyze the process, optimizing the applied condition including zinc precursor concentration, pH and the effect of dispersing agent namely cetyltrimethylammonium bromide surfactant (CTAB). The treated samples were further characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and energy-dispersive spectroscopy (EDX). Photocatalytic activities of the treated samples were assessed based on the ability of fabrics to degrade Methylene Blue dye stain under sunlight irradiation. The effect of synthesis parameters on photocatalytic activities (self-cleaning) was statistically optimized. Moreover, for evaluating the sonocatalytic efficiencies of the samples Reactive Blue 2 was applied and the activities were studied by visible spectroscopy. The cotton/polyester samples possessed multifunctional properties including self-cleaning, sonocatalytic, antibacterial, antifungal, low cytotoxicity and enhanced mechanical properties.